Guidance and Ethical Considerations for Undertaking Transgender Health Research and Institutional Review Boards Adjudicating this Research - Adams, Noah; Pearce, Ruth; Veale, Jaimie; Radix, Asa; Castro, Danielle; Sarkar, Amrita; Thom, Kai Cheng (Transgender health, 2017)
The purpose of this review is to create a set of provisional criteria for Institutional Review Boards (IRBs) to refer to when assessing the ethical orientation of transgender health research proposals. We began by searching for literature on this topic using databases and the reference lists of key articles, resulting in a preliminary set of criteria. We then collaborated to develop the following nine guidelines: (1) Whenever possible, research should be grounded, from inception to dissemination, in a meaningful collaboration with community stakeholders; (2) language and framing of transgender health research should be non-stigmatizing; (3) research should be disseminated back to the community; (4) the diversity of the transgender and gender diverse (TGGD) community should be accurately reflected and sensitively reflected; (5) informed consent must be meaningful, without coercion or undue influence; (6) the protection of participant confidentiality should be paramount; (7) alternative consent procedures should be considered for TGGD minors; (8) research should align with current professional standards that refute conversion, reorientation, or reparative therapy; and (9) IRBs should guard against the temptation to avoid, limit, or delay research on this subject.